Engineered Mesenchymal Stem Cells Over-Expressing BDNF Protect the Brain from Traumatic Brain Injury-Induced Neuronal Death, Neurological Deficits, and Cognitive Impairments - Bo Young Choi; Dae Ki Hong; Beom Seok Kang; Si Hyun Lee; Seunghyuk Choi; Hyo-Jin Kim; Soon Min Lee; Sang Won Suh (MDPI AG, 2023)
Traumatic brain injury (TBI) causes transitory or permanent neurological and cognitive impairments, which can intensify over time due to secondary neuronal death. However, no therapy currently exists that can effectively treat brain injury following TBI. Here, we evaluate the therapeutic potential of irradiated engineered human mesenchymal stem cells over-expressing brain-derived neurotrophic factor (BDNF), which we denote by BDNF-eMSCs, in protecting the brain against neuronal death, neurological deficits, and cognitive impairment in TBI rats. BDNF-eMSCs were administered directly into the left lateral ventricle of the brain in rats that received TBI damage. A single administration of BDNF-eMSCs reduced TBI-induced neuronal death and glial activation in the hippocampus, while repeated administration of BDNF-eMSCs reduced not only glial activation and delayed neuronal loss but also enhanced hippocampal neurogenesis in TBI rats. In addition, BDNF-eMSCs reduced the lesion area in the damaged brain of the rats. Behaviorally, BDNF-eMSC treatment improved the neurological and cognitive functions of the TBI rats. The results presented in this study demonstrate that BDNF-eMSCs can attenuate TBI-induced brain damage through the suppression of neuronal death and increased neurogenesis, thus enhancing functional recovery after TBI, indicating the significant therapeutic potential of BDNF-eMSCs in the treatment of TBI.